2019
DOI: 10.3991/ijet.v14i19.11208
|View full text |Cite
|
Sign up to set email alerts
|

The Science Process Skills of Prospective Biology Teachers in Plant Cell Material Based on Gender

Abstract: This study aims to describe prospective biology teachers' science process skills in plant cell material. Components of basic process skills such as (1) observing, (2) connecting, and (3) inference, and integrated process skills such as (4) analysis, (5) hypothesis, and (6) defining variables operationally, become the science process skills components examined in this study. This research is a descriptive-quantitative study with survey method to identify science process skills of 100 prospective biology teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Even though this study is performed among students with different opinions on gender equality, most of the respondents support the right of women to selfdetermination in choosing a life path, considering this an internal matter of a family. The trend of this attitude among new generations who have grown up in a digital environment is confirmed by many studies [6,28,29]. The results also show that men and women have the same social expectations of a traditional women's role.…”
Section: Source: Elaborated By the Authorssupporting
confidence: 62%
See 1 more Smart Citation
“…Even though this study is performed among students with different opinions on gender equality, most of the respondents support the right of women to selfdetermination in choosing a life path, considering this an internal matter of a family. The trend of this attitude among new generations who have grown up in a digital environment is confirmed by many studies [6,28,29]. The results also show that men and women have the same social expectations of a traditional women's role.…”
Section: Source: Elaborated By the Authorssupporting
confidence: 62%
“…Furthermore, the results of the current study regarding the importance of the social role of higher education in digital environment in overcoming gender problems are confirmed by other multiple research. Asy'ari et al [29] shows that The Science Process Skills for all stages of scientific research are more developed in men, but does not investigate the reasons for this result. The reasons may have a social origin, restrictions associated with a greater burden of motherhood and housekeeping, etc.…”
Section: Source: Elaborated By the Authorsmentioning
confidence: 98%
“…Science process skills are thinking skills that are able to answer the demands of learning in accordance with the principles of constructivism (Asy'ari & Fitriani, 2017). Science process skills are one of the important skills to be developed in learning because they can help students learn science process skills or inquiry skills to solve problems (Verawati et al, 2014), foster concepts (Doyan et al, 2021), and make students active in experimenting, taking responsibility, and being confident (Asy'ari et al, 2019). (Feyziȯğlu, 2009) explains that PPP is the ability to apply the steps of the scientific method to understand, apply and discover knowledge scientifically.…”
Section: Introductionmentioning
confidence: 99%
“…Such condition is thought to be the reason for students' low SPS [20,22]. The pre-service teachers' SPS is generally in moderate category, with hypothesis and defining variables operationally indicators as the lowest score [23]. Those findings indicate the low level of students' high-level thinking skills: critical thinking, problem solving, creative thinking, decision making and meta cognition [24].…”
mentioning
confidence: 99%
“…Furthermore stated that 81% of pre-service teachers have critical thinking skills and critical analysis with criteria that have not yet appeared or are still underdeveloped, while only 19% are categorized as developing or developing well [28], whereas Gelder found that students' metacognition abilities were generally in low category [29].Furthermore, recommends that some components of metacognition awareness such as information management system (IMS), monitoring (M), evaluation (E), and debugging (D) must be maximized in the learning process [30]. The high-level thinking skills described were very important to be mastered by students in understanding science comprehensively and SPS was claimed to be a gateway to mastering these skills [6,8,23].…”
mentioning
confidence: 99%